Iron reduction by the deep-sea bacterium Shewanella profunda LT13a under subsurface pressure and temperature conditions - Picard, Aude; Testemale, Denis; Wagenknecht, Laura; Hazael, Rachael; Daniel, Isabelle (Frontiers in Microbiology, 2015)
Microorganisms influence biogeochemical cycles from the surface down to the depths of the continental rocks and oceanic basaltic crust. Due to the poor recovery of microbial isolates from the deep subsurface, the influence of physical environmental parameters, such as pressure and temperature, on the physiology and metabolic potential of subsurface inhabitants is not well constrained. We evaluated Fe(III) reduction rates and viability, measured as colony-forming ability, of the deep-sea piezophilic bacterium Shewanella profunda LT13a over a range of pressures (0-125 MPa) and temperatures (4-37°C) that included the in situ habitat of the bacterium isolated from deep-sea sediments at 4500 m depth below sea level. S. profunda LT13a was active at all temperatures investigated and at pressures up to 120 MPa at 30°C, suggesting that it is well adapted to deep-sea and deep sedimentary environments. Average initial cellular Fe(III) reduction rates only slightly decreased with increasing pressure until activity stopped, suggesting that the respiratory chain was not immediately affected upon the application of pressure. We hypothesize that, as pressure increases, the increased energy demand for cell maintenance is not fulfilled, thus leading to a decrease in viability. This study opens up perspectives about energy requirements of cells in the deep subsurface.